The Role of History in The Research on Sufism - Khatamov Tokhir Abdumutalovich (Indonesian Journal Publisher, 2025)
In recent years, as a result of reforms in the field of science and education in our country, opportunities for studying the teachings of Sufism in the fields of history and Islamic studies have been expanding. Sufism is an amazing spiritual and cultural phenomenon of Islam, which was studied by individual Christian researchers who found themselves in the Muslim world, observing the lifestyle, ritual practices, beliefs of fakirs, dervishes, and feasts. This article analyzes the scientific study of Sufi teachings from the perspective of history and Islamic studies during the years of independence. Additionally, it provides scientific and historical conclusions on the methods of source criticism, historical processes, and the analysis of periods in research studies